IMPELEMENTASI MEDIA INTERAKTIF MONOPOLI DAN KARTU BACA UNTUK LITERASI ANAK PMI MALAYSIA - Aqila, Syarla; Azizah, Siti Nur (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
This community service aims to explore the application of interactive game-based educational media in improving basic literacy, reading, writing and arithmetic skills, and national insight in children of Indonesian Migrant Workers (PMI) living in Malaysia. Access to adequate education is a major challenge for children of Indonesian citizens abroad, especially in understanding fundamental basic literacy materials. The learning program designed using educational games, such as reading card games and monopoly, aims to provide a fun and effective learning experience. This community service uses a social approach involving groups of PMI children in Malaysia as subjects of community service. The implementation of this community service activity was carried out through pre-test and post-test methods as well as observation of student participation in learning activities. The results of community service showed a significant increase in students' basic literacy skills and national insight after participating in this game-based program. This program has proven effective in motivating students to learn and improving their understanding of basic literacy and Indonesian national identity. In addition, this method also provides opportunities for students to interact socially, develop teamwork skills, and understand the importance of national values.